THE INFLUENCE OF PHYSICAL AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEES' WORK MOTIVATION AT THE OFFICE OF PUBLIC WORKS AND SPATIAL PLANNING OF SOUTH SULAWESI PROVINCE - Abdillah Khofiyal Luthfi; Andi Mustika Amin; Tenri Sayu Puspitaningsih Dipoatmodjo; Widhi Nugraha Sumiharja Darmawinata (Universitas Negeri Makassar, 2025)
Abstract: This study aims to analyze the influence of physical and non-physical work environment on employee work motivation at the Public Works and Spatial Planning Office of South Sulawesi Province, whether the physical and non-physical work environment has a significant influence. This study uses a quantitative approach with a survey method conducted on employees of the Public Works and Spatial Planning Office of South Sulawesi Province. Data were collected through observation, documentation, and questionnaires distributed to 65 employees as samples, the sampling method is the saturated sampling method and analyzed using differential statistical analysis techniques, namely multiple regression analysis. The results of the study indicate that the physical and non-physical work environment on work motivation has a positive and significant effect both partially and simultaneously. These findings indicate that a good and comfortable physical and non-physical work environment can effectively increase work motivation in the organization. Thus, it is recommended that the Public Works and Spatial Planning Office of South Sulawesi Province continue to develop a positive work environment to improve better work motivation.Keywords: Physical work environment, non-physical work environment, work motivation